2016
DOI: 10.1158/0008-5472.can-16-0752
|View full text |Cite|
|
Sign up to set email alerts
|

EpCAM-Regulated Transcription Exerts Influences on Nanomechanical Properties of Endometrial Cancer Cells That Promote Epithelial-to-Mesenchymal Transition

Abstract: Overexpression of epithelial cell adhesion molecule (EpCAM) has been implicated in advanced endometrial cancer, but its roles in this progression remain to be elucidated. In addition to its structural role in modulating cell-surface adhesion, here we demonstrate that EpCAM is a regulatory molecule in which its internalization into the nucleus turns on a transcription program. Activation of EGF/EGFR signal transduction triggered cell-surface cleavage of EpCAM, leading to nuclear internalization of its cytoplasm… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
54
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(57 citation statements)
references
References 49 publications
3
54
0
Order By: Relevance
“…Among exosomal proteins, TGF-β1 and MAGE3/6 can be used as reliable biomarkers to discriminate between benign and malignant ovarian tumors, or to ascertain the efficacy of chemotherapy [119]. Although epithelial cell adhesion molecule (EpCAM) was demonstrated to promote epithelial-mesenchymal transition in advanced stages of endometrial cancer [152], studies indicated that EpCAM is not a robust biomarker to classify exosomes derived from benign and malignant ovarian tumors [134] or to detect early stages of the pathology [153]. Besides EpCAM, several exosomal proteins were identified to be overexpressed in ovarian cancer, including proliferation cell nuclear antigen (PCNA), tubulin beta-3 chain (TUBB3), epidermal growth factor receptor (EGFR), apolipoprotein E (APOE), claudin 3 (CLDN3), fatty acid synthase (FASN), ERBB2, and L1CAM (CD171) [127].…”
Section: Extracellular Vesicles As Biomarkers-new Diagnostic Toolsmentioning
confidence: 99%
“…Among exosomal proteins, TGF-β1 and MAGE3/6 can be used as reliable biomarkers to discriminate between benign and malignant ovarian tumors, or to ascertain the efficacy of chemotherapy [119]. Although epithelial cell adhesion molecule (EpCAM) was demonstrated to promote epithelial-mesenchymal transition in advanced stages of endometrial cancer [152], studies indicated that EpCAM is not a robust biomarker to classify exosomes derived from benign and malignant ovarian tumors [134] or to detect early stages of the pathology [153]. Besides EpCAM, several exosomal proteins were identified to be overexpressed in ovarian cancer, including proliferation cell nuclear antigen (PCNA), tubulin beta-3 chain (TUBB3), epidermal growth factor receptor (EGFR), apolipoprotein E (APOE), claudin 3 (CLDN3), fatty acid synthase (FASN), ERBB2, and L1CAM (CD171) [127].…”
Section: Extracellular Vesicles As Biomarkers-new Diagnostic Toolsmentioning
confidence: 99%
“…Hsu and colleagues reported on EGF/EGFR-triggered activation of regulated intramembrane proteolysis (RIP) of EpCAM that induces an EMT phenotype (1). This finding is of utmost interest, as it might explain contradicting effects of EpCAM on adhesion, proliferation, and invasion and shed light on EpCAM-based plasticity in cancer progression.…”
mentioning
confidence: 98%
“…Secondly, Epithelial-to-Mesenchymal Transition (EMT) is an important step towards the invasion and metastasis of cancer (19). Hsu et al demonstrated that epithelial cell adhesion molecule (EpCAM)-regulated transcription exerted in uences on nanomechanical properties of EC cells, which promotes EMT (20). Last, a hospitalbased case-control study examined the association between various polymorphisms in base excision repair (BER) DNA pathway genes (OGG1, MUTYH, XRCC1, APEX1, and PARP1) among Japanese postmenopausal women with and without endometrial cancer and found some worthful interaction (21).…”
Section: Discussionmentioning
confidence: 99%
“…GO terms with Pvalue < 0.05 were selected and ranked by enrichment score (-log10 (P-value)). Among the BP terms, response to cholesterol, epithelial to mesenchymal transition, and base-excision repair have been reported to be associated with tumor (6,(18)(19)(20)(21). In MF terms, WNT-activated receptor activity and WNT-protein binding might play a role in tumors.…”
Section: Go and Kegg Pathway Analysesmentioning
confidence: 99%